2004
DOI: 10.1021/jp0313270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Volume Fraction on the Average Flocculation Rate

Abstract: Brownian dynamics simulations are used to study the effect of the volume fraction of internal phase (10 -5 e φ e 0.40) on the flocculation rate (k f ) of oil in water (O/W) emulsions. To cover the typical range of Hamaker constants, its characteristic value for a bitumen emulsion (A ) 1.24 × 10 -19 J) and its typical order of magnitude for a latex dispersion (A ) 1.24 × 10 -21 J) were used. Account of hydrodynamic interactions was made, using a new methodology [Urbina-Villalba et al. Phys. ReV. E 2003, 68, 061… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 35 publications
6
40
0
Order By: Relevance
“…The curves of n versus t show a progressive decrease as a function of time, as is usually exhibited in the case of fast aggregation. For a flocculating-coalescing emulsion of nondeformable drops where DV T B 12.7k B T, ESS [10,54] confirm the validity of Eq. 23, provided that the number of aggregates is counted as prescribed by Danov et al [11].…”
Section: Use Of the Theory Of Smoluchowski For Prediction Of Emulsionsupporting
confidence: 54%
“…The curves of n versus t show a progressive decrease as a function of time, as is usually exhibited in the case of fast aggregation. For a flocculating-coalescing emulsion of nondeformable drops where DV T B 12.7k B T, ESS [10,54] confirm the validity of Eq. 23, provided that the number of aggregates is counted as prescribed by Danov et al [11].…”
Section: Use Of the Theory Of Smoluchowski For Prediction Of Emulsionsupporting
confidence: 54%
“…However, they demonstrated that if the coalescence rate of an emulsion is significantly faster than the flocculation rate, and big drops are counted as single particles, the expression of Smoluchowski for the total number of aggregates is recovered. This result was repeatedly validated by ESS of non-deformable drops [103,104]. In fact, an alternative expression for the total number of aggregates was deduced [103].…”
Section: Flocculation Of Oil Dropsmentioning
confidence: 58%
“…32. Despite these limitations and the ones previously mentioned regarding the effect of polydispersity, the mixed flocculation-coalescence rates observed at high ionic strength (Tables 5 and 6) are of the same order of magnitude as the one predicted by Emulsion Stability Simulations (ESS) for the case of very dilute emulsions in the absence of a repulsive force is k f = k FC = 6.4 × 10 −18 m 3 s −1 [103].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations